2021
DOI: 10.1155/2021/6666117
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Encephalitis in Tunisia: Report of a Pediatric Cohort

Abstract: Background. Autoimmune encephalitis (AE) is a rapidly progressive encephalopathy caused by antibodies targeting neurons in the central nervous system generating specific immune responses. It is increasingly recognized in children. Objective. To describe clinical, neuroimaging, and laboratory features, treatment, and outcome in a cohort of Tunisian children with AE. Methods. We conducted a retrospective review of the medical records of all children attending the Department of Child and Adolescent Neurology (Tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Brain MRI is one of the etiological examinations for initial epilepsy or encephalitis, especially the abnormal signal of T2/FLAIR in one or both medial temporal lobes could indicate AE [ 23 ]. Our study showed that 6/23 (26.1%) patients in the AE group had abnormal neuroimaging findings, supporting the findings of previous studies [ 24 ]. Although the results of multivariate analysis showed that brain MRI could not be used as an independent indicator for early prediction ( P = 0.807), the abnormal brain MRI lesions in a few patients with AE could be reversibly changed with immunotherapy (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Brain MRI is one of the etiological examinations for initial epilepsy or encephalitis, especially the abnormal signal of T2/FLAIR in one or both medial temporal lobes could indicate AE [ 23 ]. Our study showed that 6/23 (26.1%) patients in the AE group had abnormal neuroimaging findings, supporting the findings of previous studies [ 24 ]. Although the results of multivariate analysis showed that brain MRI could not be used as an independent indicator for early prediction ( P = 0.807), the abnormal brain MRI lesions in a few patients with AE could be reversibly changed with immunotherapy (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, reports of anti-Ma2-associated encephalitis in childhood are extremely rare, and an autoimmune origin appears to have been more likely in this case than a paraneoplastic mechanism [2]. To our knowledge, only seven pediatric cases of anti-Ma2-associated neurological symptoms have been reported to date (Table 1) [2][3][4][5]. There were three male and four female patients, with a median age of 4 years.…”
Section: B Cmentioning
confidence: 97%
“…The first involves a 17-year-old adolescent with paraneoplastic limbic encephalitis due to Hodgkin lymphoma, and the second concerns a 12-year-old-girl witch encephalitis, where oncological evaluation yielded negative results. 10,11 Here, we present a rare case of a 3-year-old girl with anti-SOX1 antibodies post-varicella, and no associated malignancy.…”
Section: Introductionmentioning
confidence: 95%